2023
DOI: 10.1111/jdv.19565
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic endotypes in paediatric atopic dermatitis depend on immunotype, lipid composition and microbiota of the skin

A. M. Andersson,
A. C. Ingham,
S. M. Edslev
et al.

Abstract: BackgroundAtopic dermatitis (AD) endotypes differ with ethnicity. We examined the skin microbiota, cytokine‐, and lipid‐profiles in Greenlandic Inuit and Danish children with AD.Methods25 Inuit children with AD and 25 Inuit control children were clinically examined and compared to previously collected data from 25 Danish children with AD. Skin tape strips and skin swabs were collected from lesional and non‐lesional skin. Levels of cutaneous immune biomarkers, free sphingoid bases and their (glycosyl)ceramides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The observed differences in SC lipid composition between the AD patients and the controls align with existing literature. Numerous studies have highlighted a reduction in ceramide chain length in AD patients [ 4 , 7 , 21 ], with a decrease in EO CERs and increase in C34 CERs, being more pronounced in lesional than non-lesional skin [ 7 , 22 ]. In our study, a non-significant elevation in the average ceramide chain length was noted in the control group compared with AD patients ( p = 0.056).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed differences in SC lipid composition between the AD patients and the controls align with existing literature. Numerous studies have highlighted a reduction in ceramide chain length in AD patients [ 4 , 7 , 21 ], with a decrease in EO CERs and increase in C34 CERs, being more pronounced in lesional than non-lesional skin [ 7 , 22 ]. In our study, a non-significant elevation in the average ceramide chain length was noted in the control group compared with AD patients ( p = 0.056).…”
Section: Discussionmentioning
confidence: 99%
“…In previous SC studies, tape strips no. 3 or 4 have mostly been used for lipid measurements [ 22 , 29 , 30 ], which eases comparisons with our results, although others have been using several tapes pooled together [ 31 ]. Further, SC lipids and especially the CERs, which were the main interest of this study, have been shown to have a limited variability according to depth [ 16 ].…”
Section: Discussionmentioning
confidence: 99%